Evaluating environmental commitments to COP21 and the role of economic complexity, renewable energy, financial development, urbanization, and energy innovation: Empirical evidence from the RCEP countries. (January 2022) - Bashir, Muhammad Farhan; MA, Benjiang; Hussain, Hafezali Iqbal; Shahbaz, Muhammad; Koca, Kemal; Shahzadi, Irum
Abstract: Despite extensive research to address the impact of environmental reforms under the Paris Climate Agreement, current literature has failed to provide sufficient insights into Regional Comprehensive Economic Partnership (RCEP) countries. To this end, the current study attempts to address the impact of the economic complexity on environmental quality in the presence of renewable energy consumption, financial development, urbanization and energy innovation in RCEP countries from 1990 to 2019. Our empirical estimates confirm a significant association between environmental quality, economic complexity index, renewable energy consumption, financial development, urbanization and energy innovation in the short-run and long run. Based on extensive econometric analysis (CS-ARDL, AMG, PMG, FMOLS, and DOLS), we conclude that economic complexity, renewable energy, and energy innovation effectively mitigate environmental degradation. At the same time, financial development and urbanization have an adverse impact on the environment. These findings have extensive policy implications for policymakers and environmental stakeholders, who are aiming to achieve sustainable energy policy and economic growth to meet the environmental commitments under Paris Climate Agreement. Highlights: The association between economic complexity and environmental quality is assessed. CS-ARDL, AMG, PMG, FMOLS and DOLS are used to evaluate RCEP economies data. Economic complexity has a significant and negative impact on environmental quality. Future environmental reforms are key towards fulfilling environmental targets.